2018
DOI: 10.1111/jphp.13042
|View full text |Cite
|
Sign up to set email alerts
|

The protective effects of Δ9-tetrahydrocannabinol against inflammation and oxidative stress in rat liver with fructose-induced hyperinsulinemia

Abstract: Objectives A large amount of fructose is metabolized in the liver and causes hepatic functional damage. Δ9‐tetrahydrocannabinol (THC) is known as a therapeutic agent for clinical and experimental applications. The study aims to investigate the effects of THC treatment on inflammation, lipid profiles and oxidative stress in rat liver with hyperinsulinemia. Methods Sprague‐Dawley rats were divided into groups: control, fructose (10% fructose in drinking water for 12 weeks), THC (1.5 mg/kg/day for the last 4 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Δ9- THC had no effects on insulin at 1.5 or 3.0 mg/kg/day across life stages ( Beydogan et al, 2019 , Coskun and Bolkent, 2014 , Gillies et al, 2020 ).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Δ9- THC had no effects on insulin at 1.5 or 3.0 mg/kg/day across life stages ( Beydogan et al, 2019 , Coskun and Bolkent, 2014 , Gillies et al, 2020 ).…”
Section: Resultsmentioning
confidence: 93%
“…At 1.5 mg/kg/day Δ9- THC dose, Sprague-Dawley rats treated for 28 days by i.p. in adolescence showed slight but not significant decreases in body weight ( Beydogan et al, 2019 ). Decreased body weights in adolescent male Fischer 344 and Long-Evans rats were seen at higher doses (5.0 mg/kg/day: gavage; 5.6 mg/kg/day: i.p.)…”
Section: Resultsmentioning
confidence: 99%
“…Hernandez-Rodas et al [64] demonstrated significantly decreased hepatic NrF2 DNA binding and increased hepatic NF-κB DNA binding in male C57BL/6J mice fed with a high-fat diet for 12 weeks. Beydogan et al [65] showed that the number of NF-ҡB immunopositive cells increased in Sprague-Dawley rats that received 10% fructose in drinking water for 12 weeks. Some molecular effects of cannabinoids depend on NrF2-NF-κB crosstalk.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin, as anticipated, caused a statistically significant decrease in the fasting serum insulin levels in the rats given DHT+f. Concurrent fructose consumption may have led to structural changes in pancreatic cells, resulting in hyperinsulinemia and an inability to control serum blood glucose, which would have indicated insulin resistance [33,34].…”
Section: Oral Glucose Tolerance Test and Insulin Resistancementioning
confidence: 99%